Recurrent pattern of extreme fire weather in California. (31st August 2021) - Son, Rackhun; Wang, S-Y Simon; Kim, Seung Hee; Kim, Hyungjun; Jeong, Jee-Hoon; Yoon, Jin-Ho
Abstract: Historical wildfire events in California have shown a tendency to occur every five to seven years with a rapidly increasing tendency in recent decades. This oscillation is evident in multiple historical climate records, some more than a century long, and appears to be continuing. Analysis shows that this 5–7 year oscillation is linked to a sequence of anomalous large-scale climate patterns with an eastward propagation in both the ocean and atmosphere. While warmer temperature emerges from the northern central Pacific to the west coast of California, La Niña pattern develops simultaneously, implying that the lifecycle of the El Niño-Southern Oscillation that takes multiple years to form could be a trigger. The evolving patterns of the Pacific-to-North America atmospheric teleconnection suggest the role of tropical and subtropical forcing embedded in this lifecycle. These results highlight the semi-cyclical hydrological behavior as a climate driver for wildfire variability in California.